Penerapan Sistem Informasi Manajemen Dalam Meningkatkan Kualitas Pelayanan Administrasi Di Kantor PT. Taspen (Persero) Kendari - Desriyani, Desriyani; Mustafa, La Ode; Batara, Suriyani Bunga (REZ PUBLICA, 2020)
This study aims to identify and describe the application of management information systems in improving the quality of administrative services at the PT. TASPEN (Persero) Branch Kendari with the research method used is descriptive qualitative, a description of the results of observations, interviews, and documentation studies, the data that has been obtained will be analyzed qualitatively and described in descriptive form. The results of the study aim that the Application of Management Information Systems in the PT. TASPEN (Persero) Kendari Branch Is Not Effective Enough, the hardware dimensions of the program have been well implemented, the dimensions of the software program have been implemented quite well, the database dimensions of the program have not been maximized, the dimensions of this program procedure have been implemented quite well, then the dimensions of program officers have been implemented. Well done. Quality of Administration Services in the Office of PT. TASPEN (Persero) Kendari Branch is not good enough, the dimensions of reliability, responsiveness, assurance, attention have been carried out well, while the dimensions of this physical evidence are not good enough.